THE REPRESENTATION OF SECULARISM IN ISLAM UNDER MODERN TURKEY DEPICTED IN ORHAN PAMUKS’S SNOW - KHOIRIYAH AL HARITS, MARIFATUL (LANGUAGE HORIZON, 2019)
Representation is a part of literary study that subjectively viewed the cultural context and power in a society. This is kind of language used by people to say and represent the world meaningfully. In 2002, Nobel Prize author ? Orhan Pamuk? Published his first political-historical novel entitled Snow, the novel creates a public debate during its publication. The issue of Islam against secularist appeared in this novel, which presents the struggle of Headscarf girl and Islam Fundamentalist in Kars City. This study aims on three different parts to portray the representation of Islam, they are: Representation of Secularism in Islam under the Media, Headscarf culture and how Ka as the main character views the tensions between Modern and Traditional city. By focusing on the topic that related to Islam and its problem with Secular State in the novel, this study captured the representation of Secularism in Islam in different aspect such as representation of Secularism in Islam and Islam itself under the Media, secularist and political Islam. Similarly, headscarf as a part of religious dress code and secular media portray in this study that is achieved by application of Cultural and Representation theory from Stuart Hall and discussed three elements of representation such as: Reflective, Intentional and constructionist. Reffering to the findings, the study concludes that the representation of Islam under Modern Turkey presents the depiction of Islamic figure. Keywords: Representation, Islam, Secularism, Headscarf, Veils, Turkey, Modern and Traditional.